Needle in a timestack [videorecording (DVD)] - Ridley, John, 1965-; Ridley, John, 1965-; Erivo, Cynthia, 1987-; Odom, Leslie, Jr., 1981-; Bloom, Orlando, 1977-; Pinto, Freida, 1984-; Oliveira, Laysla de, 1992-; Silverberg, Robert (Lionsgate, 2021)
In a world where time travel is possible, Nick and Janine's happy marriage starts falling apart when Janine's ex-husband travels through time to break up their relationship.